(untitled) (Research, Society and Development, 2022)
Objective: Investigate evidence on the role of pharmacists in the field of veterinary drugs intended for companion animals. Method: Integrative review. Results: 18 works were retrieved, 14 of which were cross-sectional studies, 2 letters to the editor, 1 experience report and 1 integrative review. The veterinary pharmaceutical market has gained space within the pharmaceutical profession. Pharmaceutical services, such as pharmaceutical care to ensure the quality use of medicines for veterinary use, have market potential. Conclusion: There is evidence that the pharmacist is important to the field of veterinary medicine. It is an essential requirement that he be qualified – with appropriate training – to handle veterinary prescriptions and companion animals. It also requires professional integration between pharmacists and veterinarians.